Recycled quarry opens in Kenya - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
Large limestone quarries near Mombasa on the Kenya coast which once supplied a nearby cement works, have been reopened, this time to the public. Over twenty years ago a Swiss agronomic engineer from Baobab Farm Ltd put forward the idea of planting...